Positive electrode material and manufacturing method thereof

By covering the outer surface of the positive electrode material with a core-shell structure and further covering the liquid-retaining material layer, the battery safety problem caused by the positive electrode material releasing oxygen under high temperature and high pressure is solved, and higher battery safety is achieved Performance and stability.

CN119419226AActive Publication Date: 2025-02-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411328261.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-11
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing positive electrode materials release a large amount of oxygen under high temperature and high pressure, causing the battery separator to shrink, short circuit and thermal runaway, affecting the battery safety performance.

Method used

The outer surface of the positive electrode active material is coated with a coating material particles with a core-shell structure. The core is a porous adsorption material and the outer shell layer is a deoxygenation material. The liquid-retaining material layer is further coated to form a multi-layer structure. This structure can effectively adsorb and remove oxygen released by the positive electrode material, improving the safety performance of the battery.

Benefits of technology

Through the multi-layer structure design, it can effectively adsorb and remove oxygen released from the positive electrode material, improve the safety performance of the battery, delay the thermal runaway of the battery cell, and improve the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419226A_ABST
    Figure CN119419226A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a positive electrode material and a manufacturing method thereof, the material comprises a positive electrode active material and a coating layer, and the coating layer coats the outer surface of the positive electrode active material; the coating layer comprises coating material particles, the coating material particles have a core-shell structure, the core of the core-shell structure is an adsorption material, and the shell layer of the core-shell structure is a deoxidation material; the adsorption material comprises a porous adsorption material; the porous adsorption material in the core-shell structure can directly absorb oxygen released by the coated positive electrode active material, and the deoxidation material of the shell layer of the core-shell structure coating the outer surface of the adsorption material can directly capture adsorbed oxygen molecules from the adsorption material, so that the adsorption material can continue to vacate an adsorption space; the adsorption efficiency and the safety performance are improved; oxygen released by the positive electrode active material in the positive electrode material can be effectively adsorbed and removed, and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to positive electrode materials and methods for manufacturing the same. Background Art

[0002] At present, high nickel content in positive electrode materials is one of the important directions to improve battery energy density. However, the increase in nickel content will cause the positive electrode material to undergo phase change at high temperature and high pressure and release a large amount of oxygen. The released oxygen will react with the electrolyte and the negative electrode in the battery to generate a large amount of heat, causing the diaphragm to shrink and break, and short circuit to cause thermal runaway. Therefore, inhibiting the release of oxygen and heat from the positive electrode material and increasing the stability of the positive electrode material can effectively delay the occurrence of thermal runaway in the battery cell and thus improve the safety performance of the battery cell.

[0003] At present, the main methods for inhibiting the release of oxygen and heat generation from the positive electrode materials of batteries are to add porous oxygen absorbing additives to the positive electrode sheets and to coat a layer of metal element on the surface of the positive electrode materials. Adding porous oxygen absorbing additives to the positive electrode sheets can absorb the oxygen released by the positive electrode materials, thereby alleviating the release of oxygen from the positive electrode. However, the conductivity of such materials is general, which will affect the conduction of electrons in the active layer, increase the internal resistance of the battery cell, and affect the performance of the battery cell. In addition, due to the insufficient contact between the oxygen absorber and the active material, there is a risk of untimely absorption or omission of the oxygen released by the positive electrode. When a layer of metal element is coated on the surface of the positive electrode material, the metal element can undergo an oxidation reaction with the oxygen released by the material to achieve the effect of absorbing oxygen. However, during the cycle, the metal element is separated from the positive electrode material due to material deformation and rupture, forming metal foreign matter, which can easily cause increased self-discharge and internal short circuit, increasing safety hazards. Summary of the invention

[0004] In order to solve the problems of the prior art, the present application provides a positive electrode material and a method for manufacturing the same, which can effectively adsorb and remove oxygen released by the positive electrode active material inside the positive electrode material, thereby improving the safety performance of the battery.

[0005] Specifically, in a first aspect, the present application provides a positive electrode material, the material comprising a positive electrode active material and a coating layer, the coating layer coating the outer surface of the positive electrode active material;

[0006] The coating layer comprises coating material particles, the coating material particles have a core-shell structure, the core of the core-shell structure is an adsorption material, and the outer shell layer of the core-shell structure is a deoxidation material; the adsorption material comprises a porous adsorption material.

[0007] In some embodiments, the coating layer has a thickness of 0.5-3 μm; the coating material particles further include a liquid retaining material layer, and the liquid retaining material layer is coated on the outer surface of the deoxidizing material.

[0008] In some embodiments, the mass ratio of the adsorbent material, the deoxidizing material and the liquid retaining material layer is (80-90): (5-10): (5-10);

[0009] and / or,

[0010] The liquid retaining material includes a mixture of one or more of polyacrylate, polyacrylic acid diethyl ester, and polymethyl methacrylate;

[0011] and / or,

[0012] The thickness of the liquid retaining material layer is 200nm-1000nm.

[0013] In some embodiments, the porous adsorption material includes a mixture of one or more of a porous carbon material, a porous MOF, a porous ZIF, and a porous silicon-carbon material;

[0014] and / or, the deoxidizing material comprises a mixture of one or more of catechol, pyrogallol, p-methoxyphenol, cresol, tert-butylcatechol, p-phenylenediamine, polyethyleneimine, acetyl dopamine, ethylenediamine, and diphenylamine; and / or;

[0015] The thickness of the outer shell layer formed by the deoxidizing material is 50nm-200nm.

[0016] In some embodiments, the coating layer further comprises a conductive agent and a binder, and the mass ratio of the coating material particles to the conductive agent and the binder is (90-95): (5-10): (2-5);

[0017] And / or, the conductive agent includes a mixture of one or more of graphene, conductive graphite, and carbon nanotubes;

[0018] And / or, the binder includes a mixture of one or more of PVDF, PTFE, CMC, and PAA.

[0019] In some embodiments, the positive electrode active material includes a mixture of one or more of a nickel cobalt lithium manganese oxide ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and a layered oxide compound; preferably, the positive electrode active material includes a chemical formula of LiNi x Co y High nickel ternary material of MnO2, wherein x≥0.7.

[0020] In a second aspect, the present application provides a method for manufacturing a positive electrode material, the method comprising:

[0021] The first porous precursor material particles are prepared by synthesizing cobalt salt and 2-methylimidazole;

[0022] preparing the first porous precursor material particles and the deoxidized material into coating material particles;

[0023] Mixing the coating material particles with a conductive agent and a binder to obtain a coating layer material;

[0024] The positive electrode material is prepared by coating the coating layer material on the surface of the positive electrode active material.

[0025] In some embodiments, the mass ratio of the cobalt salt to 2-methylimidazole is 1:(3-6);

[0026] and / or,

[0027] When the first porous precursor material particles and the deoxidizing material are prepared into coated material particles, a liquid retaining material is also added;

[0028] and / or,

[0029] The mass ratio of the coating material particles to the conductive agent and the binder is (90-95):(5-10):(2-5).

[0030] In some embodiments, the step of synthesizing the cobalt salt and 2-methylimidazole to prepare the first porous precursor material particles includes:

[0031] The cobalt salt and 2-methylimidazole are uniformly mixed in a solvent to prepare a mixed solution, and then the mixture is heated to react to synthesize a three-dimensional porous precursor material;

[0032] Ball milling the three-dimensional porous precursor material to prepare first porous precursor material particles;

[0033] and / or,

[0034] The step of preparing the first porous precursor material particles, the deoxidizing material, and the liquid retaining material into coating material particles comprises:

[0035] After uniformly dispersing the first porous precursor material particles into a solution containing a deoxidizing material, centrifugally filtering and air-drying to obtain second porous precursor material particles with the deoxidizing material adsorbed on the surface;

[0036] The liquid-retaining material is ball-milled and uniformly dispersed in a solvent to prepare a polymer colloidal solution;

[0037] The polymer colloidal solution is uniformly coated on the surface of the second porous precursor material particles by spray drying, and then heated and dried to obtain coated material particles.

[0038] In some embodiments, the solvent includes at least one of water, DMF, ethylene glycol, and methanol;

[0039] and / or,

[0040] The concentration of the mixed solution is 10-100 g / L;

[0041] and / or,

[0042] The temperature of the temperature-raising reaction is 100-200°C, and the reaction time is 1-6h;

[0043] and / or,

[0044] The solvent in the solution containing the deoxidizing material is at least one of water, ethanol and methanol, and the concentration of the solution containing the deoxidizing material is 5-10 g / L;

[0045] and / or,

[0046] The spray drying temperature is 60-100°C.

[0047] According to the specific embodiments provided in this application, this application discloses the following technical effects:

[0048] In the present application, a coating layer composed of coating material particles with a core-shell structure is coated on the outer surface of the positive electrode active material, wherein the core in the core-shell structure of the coating material particles is an adsorption material that adsorbs oxygen released by the positive electrode active material, and the outer shell layer of the core-shell structure is a deoxidation material that provides hydrogen atoms required for free radicals to stabilize the oxidation reaction. The adsorption material directly absorbs the oxygen released by the coated positive electrode active material, and the deoxidation material coated on the outer surface of the adsorption material can directly capture the adsorbed oxygen molecules from the adsorption material, so that the adsorption material can continue to vacate adsorption space, thereby improving the adsorption efficiency and safety performance; it can effectively adsorb and remove the oxygen released by the positive electrode active material inside the positive electrode material, thereby improving the safety performance of the battery.

[0049] Furthermore, in the present application, the liquid retaining material is coated on the outside of the deoxidizing material, which can increase the liquid retention capacity of the lithium battery and improve the cycle capacity on the one hand, and on the other hand, due to the toughness of the polymer, improve the contact between the positive electrode active materials, reduce the contact impedance, and improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The disclosure of the present application will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present application. In addition, similar numbers in the drawings are used to represent similar components, among which:

[0051] Figure 1 is a schematic diagram of the structure of the positive electrode material provided in the embodiment of the present application;

[0052] Figure 2 It is a schematic diagram of the structure of the coating material particles provided in the embodiment of the present application.

[0053] Among them: 1. positive electrode active material; 2. coating layer; 21. adsorption material; 22. deoxidation material; 23. liquid retaining material layer. DETAILED DESCRIPTION

[0054] Some embodiments of the present application are described below with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are only used to explain the technical principles of the present application and are not intended to limit the protection scope of the present application.

[0055] As described in the background technology, the high-nickel positive electrode material will release a large amount of oxygen under high temperature and high pressure. The released oxygen reacts with the electrolyte and the negative electrode in the battery to generate a large amount of heat, resulting in the shrinkage and damage of the lithium battery diaphragm, and short circuit causes thermal runaway. At present, the electrode material is mainly inhibited from releasing oxygen and generating heat by adding porous oxygen absorption additives in the positive electrode sheet to absorb the oxygen released by the positive electrode material, and the metal element coated on the surface of the positive electrode material reacts with the oxygen released by the material to absorb oxygen. However, the addition of porous oxygen absorption additives will affect electronic conduction and the performance of the battery cell, and due to its insufficient contact with the active material, it will lead to untimely or even missed oxygen absorption. The method of coating the metal element is prone to the situation that the metal element is deformed and ruptured during the cycle of the battery, and it is easy to cause the self-discharge to increase and the internal short circuit to increase the safety hazard.

[0056] To solve the above problems, the present application creatively proposes a positive electrode material and a method for manufacturing the same, wherein a coating layer composed of coating material particles with a core-shell structure is coated on the outer surface of the positive electrode active material, wherein the core in the core-shell structure of the coating material particles is an adsorption material that adsorbs oxygen released by the positive electrode active material, and the outer shell layer of the core-shell structure is a deoxidation material that provides hydrogen atoms required for free radicals to stabilize the oxidation reaction. The adsorption material directly absorbs the oxygen released by the coated positive electrode active material, and the deoxidation material coated on the outer surface of the adsorption material can directly capture the adsorbed oxygen molecules from the adsorption material, so that the adsorption material can continue to vacate adsorption space, thereby improving the adsorption efficiency and safety performance; it can effectively adsorb and remove the oxygen released by the positive electrode active material inside the positive electrode material, thereby improving the safety performance of the battery.

[0057] The following are optional technical solutions for this application, but are not intended to limit the technical solutions provided in this application. Through the following optional technical solutions, the technical objectives and beneficial effects of this application can be better achieved and realized.

[0058] In the first aspect, the present application provides a positive electrode material, referring to Figure 1As shown, the positive electrode material includes a positive electrode active material 1 and a coating layer 2, and the coating layer 2 is coated on the outer surface of the positive electrode active material 1; the positive electrode active material 1 and the coating layer 2 coated on the outer surface of the positive electrode active material 1 form a core-shell structure with the positive electrode active material 1 as the core and the coating layer 2 as the shell.

[0059] The coating layer 2 includes coating material particles, the coating material particles have a core-shell structure, the core of the core-shell structure is the adsorption material 21, and the outer shell layer of the core-shell structure is the deoxidation material 22; the adsorption material 21 includes a porous adsorption material.

[0060] In some embodiments, the thickness of the coating layer 2 is 0.5-3 μm; optionally, the thickness of the coating layer 2 can be 0.5 μm, 0.9 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2.5 μm, 3 μm, or any thickness value within the above thickness value range. Due to space limitations and for the sake of simplicity, this application no longer exhaustively lists the specific point values ​​included in the range.

[0061] Reference Figure 2 As shown, the coating material particles further include a liquid retaining material layer 23 , and the liquid retaining material layer 23 is coated on the outer surface of the deoxidizing material 22 .

[0062] In some embodiments, the mass ratio of the adsorption material 21, the deoxidation material 22 and the liquid retaining material layer 23 is (80-90): (5-10): (5-10); and / or,

[0063] The liquid retaining material includes a mixture of one or more of polyacrylate, polyacrylic acid diethyl ester, and polymethyl methacrylate; and / or,

[0064] The thickness of the liquid retaining material layer 23 is 200 nm to 1000 nm.

[0065] Exemplarily, the mass ratio of the adsorbent material 21, the deoxidizing material 22 and the liquid retaining material layer 23 can be (80:5:5), (90:10:10), (85:7:8), (80:10:10), (90:5:5), (88:8:6) or any ratio within the above ratio range. Due to space limitations and for the sake of simplicity, this application will no longer exhaustively list the specific ratios included in the above range. The thickness of the liquid retaining material layer can be 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 760nm, 800nm, 900nm, 1000nm or any thickness value within the above thickness value range. Due to space limitations and for the sake of simplicity, this application will no longer exhaustively list the specific point values ​​included in the above range.

[0066] In some embodiments, the porous adsorption material includes a mixture of one or more of a porous carbon material, a porous MOF, a porous ZIF, and a porous silicon-carbon material;

[0067] and / or, the deoxidizing material 22 includes a mixture of one or more of catechol, pyrogallol, p-methoxyphenol, cresol, tert-butylcatechol, p-phenylenediamine, polyethyleneimine, acetyl dopamine, ethylenediamine, and diphenylamine; and / or;

[0068] The thickness of the outer shell layer formed by the deoxidation material 22 is 50nm-200nm. For example, the thickness of the outer shell layer formed by the deoxidation material can be 50nm, 70nm, 90nm, 110nm, 130nm, 150nm, 170nm, 190nm, 200nm or any thickness value within the above thickness value range. Due to space limitations and for the sake of simplicity, this application will no longer exhaustively list the specific point values ​​included in the range.

[0069] In some embodiments, the coating layer 2 further comprises a conductive agent and a binder, and the mass ratio of the coating material particles to the conductive agent and the binder is (90-95): (5-10): (2-5); and / or, the conductive agent comprises a mixture of one or more of graphene, conductive graphite, and carbon nanotubes;

[0070] And / or, the binder includes a mixture of one or more of PVDF, PTFE, CMC, and PAA.

[0071] Exemplarily, the mass ratio of the coating material particles to the conductive agent and the binder can be (90:5:2), (95:10:5), (90:10:5), (93:5:2), (94:10:5), (92.5:7:3), or any ratio within the above ratio range. Due to space limitations and for the sake of brevity, this application no longer exhaustively lists the specific ratios included in the said range.

[0072] The conductive agent is preferably carbon nanotubes, which enhance the conductivity of the coating layer. Due to the toughness of the polymer liquid retaining agent, the contact performance between the coated positive electrode materials of the present application is improved, further reducing the contact impedance and improving the comprehensive electrochemical performance of the lithium battery.

[0073] In some embodiments, the positive electrode active material 1 includes a mixture of one or more of a nickel cobalt lithium manganese oxide ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and a layered oxide compound; preferably, the positive electrode active material includes a chemical formula of LiNi x Co y A high nickel ternary material of MnO2, wherein x≥0.7. For example, x can be 0.7, 1, 2, 2.5, 3, or any other point value greater than or equal to 0.7. Due to space limitations and for the sake of brevity, this application will no longer exhaustively list the specific point values ​​included in the range.

[0074] The present application also provides a method for manufacturing a positive electrode material, the method comprising:

[0075] S1. Synthesize cobalt salt and 2-methylimidazole to prepare first porous precursor material particles.

[0076] Cobalt salt refers to a substance composed of cobalt ions and acid radicals, which may also contain a certain proportion of other ions. In the present application, the cobalt salt may be at least one of cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt nitrate or cobalt sulfate.

[0077] S2. Prepare coating material particles from the first porous precursor material particles and the deoxidizing material.

[0078] The deoxidizing material includes a mixture of one or more of catechol, pyrogallol, p-methoxyphenol, cresol, tert-butylcatechol, p-phenylenediamine, polyethyleneimine, acetyl dopamine, ethylenediamine, and diphenylamine.

[0079] S3. Mix the coating material particles with a conductive agent and a binder to obtain a coating layer material.

[0080] The conductive agent includes a mixture of one or more of graphene, conductive graphite, and carbon nanotubes, and the binder includes a mixture of one or more of PVDF, PTFE, CMC, and PAA.

[0081] S4. Coating the coating layer material on the surface of the positive electrode active material to obtain the positive electrode material.

[0082] In some embodiments, the mass ratio of the cobalt salt to 2-methylimidazole is 1:(3-6);

[0083] and / or, when the first porous precursor material particles and the deoxidizing material are prepared into coating material particles, a liquid retaining material is also added; and / or,

[0084] The mass ratio of the coating material particles to the conductive agent and the binder is (90-95):(5-10):(2-5).

[0085] Exemplarily, the mass ratio of cobalt salt to 2-methylimidazole is 1:3, 1:3.8, 1:4, 1:4.5, 1:5, 1:6, or any ratio within the above ratio range. Due to space limitations and for simplicity, this application no longer exhaustively lists the specific ratios included in the range. The mass ratio of coating material particles to conductive agent and binder is 90:5:2, 90:10:5, 95:5:2, 93:5:2, 94:10:5, 92:7:3, 91.5:8:4, or any ratio within the above ratio range. Due to space limitations and for simplicity, this application no longer exhaustively lists the specific ratios included in the range. In addition, when the first porous precursor material particles and the deoxidized material are prepared into coated material particles, a liquid retaining material is also added to coat the porous material with a layer of polymer liquid retaining material, which can increase the liquid retention amount of the lithium battery and improve the cycle capacity. On the other hand, due to the toughness of the polymer, the contact between the positive electrode active materials is improved, the contact impedance is reduced, and the electrochemical performance is improved.

[0086] In some embodiments, step S1 includes:

[0087] S11. Evenly mix the cobalt salt and 2-methylimidazole in a solvent to prepare a mixed solution, and then heat the solution to react and synthesize a three-dimensional porous precursor material.

[0088] S12, ball-milling the three-dimensional porous precursor material to prepare first porous precursor material particles.

[0089] Step S2 includes:

[0090] S21, after uniformly dispersing the first porous precursor material particles in a solution containing a deoxidizing material, centrifugally filter and air-dry to obtain second porous precursor material particles with the deoxidizing material adsorbed on the surface.

[0091] S22, ball-milling the liquid-retaining material and uniformly dispersing it into a solvent to prepare a polymer colloidal solution.

[0092] S23, uniformly coating the polymer colloidal solution on the surface of the second porous precursor material particles by spray drying, and heating and drying to obtain coated material particles.

[0093] In some embodiments, the solvent includes at least one of water, DMF, ethylene glycol, and methanol;

[0094] and / or, the concentration of the mixed solution is 10-100 g / L;

[0095] And / or, the temperature of the temperature-raising reaction is 100-200° C., and the reaction time is 1-6 hours;

[0096] and / or, the solvent in the solution containing the deoxygenating material is at least one of water, ethanol and methanol, and the concentration of the solution containing the deoxygenating material is 5-10 g / L;

[0097] And / or, the spray drying temperature is 60-100°C.

[0098] In step S21, after the first porous precursor material particles are uniformly dispersed in the solution containing the deoxidized material, vacuum stirring is performed for 6-12 hours before centrifugation filtration and air drying to obtain the second porous precursor material particles with the deoxidized material adsorbed on the surface, to ensure that the first porous precursor material particles are uniformly dispersed in the solution containing the deoxidized material.

[0099] In step S4, the coating layer material obtained by uniformly mixing the coating material particles with the conductive agent and the binder in step S3 is uniformly coated on the surface of the positive electrode active material by spray drying to obtain a positive electrode material with a coating layer.

[0100] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents and instruments used, they are all conventional products that can be purchased commercially.

[0101] Example 1

[0102] 1) Synthesis of the first porous precursor material

[0103] First, cobalt salt and 2-methylimidazole are uniformly mixed in water at a mass ratio of 1:4 to prepare a mixed solution with a solution concentration of 20 g / L. The solution is then slowly heated to 120°C and stirred for 4 hours to obtain a three-dimensional porous ZIF precursor material.

[0104] The three-dimensional porous ZIF material obtained above is ball-milled to prepare particles with a particle size of about 1 um, thereby obtaining a first porous precursor material.

[0105] 2) Preparation of coating material particles

[0106] First, the deoxygenation material catechol is dissolved in an ethanol solvent at a concentration of 8 g / L. Then, the first porous precursor material obtained above is evenly dispersed in an ethanol solution containing catechol and vacuum stirred for 6 hours. After centrifugal filtration and air-drying, the second porous precursor material particles with the deoxygenation material adsorbed on the surface are obtained. The thickness of the deoxygenation layer here is 100 nm.

[0107] The liquid-retaining material is ball-milled into a particle size of 50-200 nm, and the particle size is uniformly dispersed in a dichloroethane solution to prepare a colloidal solution with a viscosity in the range of 1000-2000 ppm to obtain a polymer colloidal solution.

[0108] Subsequently, the second porous precursor material particles obtained above are ball-milled and transferred into a fluidized bed, and the polymer colloidal solution is evenly coated on the second porous precursor material particles by spray drying. The temperature is controlled at 60°C, and the polymer is heated and dried to form a target product, i.e., coated material particles. The thickness of the liquid retention layer here is about 400nm.

[0109] 3) Preparation of positive electrode materials

[0110] The coating material particles prepared above are uniformly mixed with a conductive agent and a binder in a ratio of 90:7:3 to obtain a coating layer material, wherein the conductive agent is carbon nanotubes. The coating layer material is uniformly coated on the surface of the positive electrode active material by spray drying, and the thickness of the coating layer is 1.5 um, thereby obtaining a positive electrode material with a core-shell structure.

[0111] 4) Preparation of the active layer of the positive electrode

[0112] The conductive agent is SP (super pll conductive carbon black) and carbon nanotubes, the binder is PVDF5130, and the positive electrode current collector is 10μm aluminum foil. The positive electrode material prepared above is mixed with the conductive agent and the binder in a ratio of 97:2:1, and NMP (N-methylpyrrolidone) is added and stirred to form a uniform and stable positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector, and the coating surface density is 156g / m 2 After drying and cold pressing, the positive electrode sheet is obtained, and the compaction density is 3.4g / cm 3 .

[0113] 5) Preparation of negative electrode sheet

[0114] Graphite is used as the negative electrode active material, SP is used as the conductive agent, CMC and SBR are used as the binder, and 6μm copper foil is used as the negative electrode current collector. The negative electrode active material, conductive agent, CMC and SBR are mixed in a ratio of 96.5:1:1:1.5, deionized water is added and stirred to form a uniform and stable negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode current collector, with a coating surface density of 156g / m 2 After drying and cold pressing, the negative electrode sheet is obtained, and the compaction density is 1.5g / cm 3 .

[0115] 6) Preparation of batteries

[0116] Selection of isolation film: Polypropylene film is selected as the isolation film base film with a thickness of 12μm.

[0117] Assembly of the battery cell: Arrange the positive electrode sheet and the separator prepared above, the negative electrode sheet and the separator prepared above in sequence, and assemble them in a winding manner to obtain a battery cell.

[0118] Preparation of electrolyte: LiPF6 was dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a volume ratio of 1:1:1, with a concentration of 1.2 mol / L.

[0119] The electrolyte was injected into the dry battery cell, and after soaking for 24 hours, the battery cell was formed at 45°C. The formation process was as follows: charge at 0.05C to 3.4V, and then charge at 0.2C to 3.75V. The battery cell was completed after aging at room temperature for 24 hours.

[0120] Example 2

[0121] The difference between this embodiment and embodiment 1 is that in this embodiment, the temperature of the polymer colloidal solution prepared by uniformly dispersing the liquid-retaining material particles in the dichloroethane solvent is increased to 80° C. when it is uniformly coated on the second porous precursor material particles by spray drying.

[0122] Example 3

[0123] The difference between this embodiment and embodiment 1 is that the thickness of the coating layer in this embodiment is 3 μm.

[0124] Example 4

[0125] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness of the deoxidation layer is changed by prolonging the immersion time of the first porous precursor material in the deoxidation material solution, and the thickness is 150 nm.

[0126] Example 5

[0127] The difference between this embodiment and embodiment 1 is that in this embodiment, the thickness of the liquid retaining material layer is changed by extending the spray drying time, and the thickness is 800 nm.

[0128] Example 6

[0129] The difference between this embodiment and embodiment 1 is that in this embodiment, the particle size of the first porous precursor material is increased, which is equivalent to the increase in the ZIF ratio, and the ZIF particle size is increased to 1.5 um.

[0130] Comparative Example 1

[0131] The difference between Comparative Example 1 and Example 1 is that the thickness of the coating layer is 5 um.

[0132] Comparative Example 2

[0133] The difference between Comparative Example 2 and Example 1 is that there is no deoxidizing material layer in the coating layer.

[0134] Comparative Example 3

[0135] The difference between Comparative Example 3 and Example 1 is that there is no liquid retaining material layer in the coating layer.

[0136] Comparative Example 4

[0137] The difference between Comparative Example 4 and Example 1 is that the coating layer does not include a deoxidizing material layer or a liquid retaining material layer, and the liquid retaining agent and the deoxidizing agent are uniformly dispersed in the coating layer with the same mass.

[0138] Comparative Example 5

[0139] The difference between Comparative Example 5 and Example 1 is that the conductive carbon nanotubes are eliminated from the coating layer on the surface of the positive electrode material, and instead the conductive carbon nanotubes are dispersed in the positive electrode slurry with the same mass.

[0140] Test methods and conditions

[0141] 1. Cycle test

[0142] Cyclic performance test (tested in the Xinwei system):

[0143] Charging: 1C constant current and constant voltage charging to 4.25V, cut-off current is 0.05C, and stand for 5 minutes; Discharging: 1C constant current discharge to 2.8V, stand for 5 minutes. Completing one charging and discharging process is considered to complete one cycle.

[0144] Discharge capacity after the first cycle of 1C operation: 1C constant current and constant voltage charging to 4.25V, the cut-off current is 0.05C, and 1C constant current discharge to 2.8V. The discharge capacity measured in this step is the first cycle discharge capacity of 1C operation (recorded as C1).

[0145] Discharge capacity after 1C operation for the nth cycle: 1C constant current and constant voltage charging to 4.25V, cut-off current is 0.05C, 1C constant current discharge to 2.8V, the discharge capacity measured in this step is the 1C operation for the nth cycle discharge capacity (denoted as C n ).

[0146] Repeat the above test steps in sequence, and test repeatedly, then the Nth cycle capacity retention rate = the Nth cycle discharge capacity C n / First cycle discharge capacity C1.

[0147] 2. Hot box safety test

[0148] The hot box test conditions are to heat the battery to 130℃ at room temperature at 5℃ / min, keep it warm for 30 minutes, stop keeping the temperature constant, and observe for 1 hour; heat the ambient temperature to 130℃ again at 5℃ / min, and keep the temperature constant for 30 minutes; then heat it up at a gradient of 5℃, keep the temperature constant for 30 minutes, and so on until the battery fails. Record the failure temperature of each battery. The higher the temperature, the higher the thermal stability of the battery cell and the better the safety performance.

[0149] 3. Diaphragm resistance test

[0150] The prepared positive electrode sheets were rolled to the same thickness, and the film resistance of the sheets was tested using a four-probe resistance tester.

[0151] 4. 1C Energy Density

[0152] Charging: 1C constant current and constant voltage charging to 4.25V, cut-off current is 0.05C, and stand for 5 minutes; Discharging: 1C constant current discharge to 2.8V, and stand for 5 minutes.

[0153] Record the battery's 1C discharge capacity C0, discharge voltage V, and weigh the battery's weight m, then energy density = capacity * voltage / weight.

[0154] 5. Liquid retention test

[0155] The positive electrode sheets of the same weight were immersed in the electrolyte for 4 hours and then taken out and weighed.

[0156] The test results of the batteries and positive electrode sheets prepared in Examples 1-3 and Comparative Examples 1-5 are shown in Table 1.

[0157] Table 1

[0158]

[0159] From the test results in Table 1, we can see that:

[0160] 1) Compared with Comparative Examples 1-5, the batteries prepared in Examples 1-6 have excellent cycle performance.

[0161] 2) Compared with Comparative Examples 1-5, the batteries prepared in Examples 1-6 have excellent density.

[0162] 3) Compared with Comparative Examples 1-5, the batteries prepared in Examples 1-6 can have excellent liquid retention coefficients while ensuring excellent battery energy density and cycle performance. In particular, as the thickness of the coating layer increases in Example 1, Example 3 and Comparative Example 1, the liquid retention coefficient of the battery can be improved, but too high a thickness of the functional layer will also lead to an increase in ionic impedance and a decrease in energy density, so overall there are disadvantages.

[0163] 4) Compared with Comparative Examples 1-5, the batteries prepared in Examples 1-6 have higher hot box failure temperatures and better safety performance. Comparing Examples 1-6 with Comparative Example 2, there is no deoxidation layer in the coating structure, and it can be found that the hot box failure temperature is significantly reduced. It is speculated that the oxygen released by the positive electrode cannot be continuously adsorbed, resulting in a decrease in the hot box temperature; Comparing Examples 1-6 with Comparative Example 3, the coating structure does not contain a polymer liquid-retaining material layer, and it is obviously found that the diaphragm resistance deteriorates. It is speculated that the toughness coating of the polymer layer is lacking. At this time, the contact between the functional coating layers deteriorates, so the conductive diaphragm resistance increases, deteriorating the electrochemical performance; Comparing Examples 1-6 with Comparative Example 4, although all the component proportions are the same as in Example 1, the diaphragm resistance also increases a lot. It is speculated that the contact between the active materials is deteriorated due to the uneven toughness zone on the surface of the functional layer, which also deteriorates the battery performance; By comparing Comparative Example 5 with Examples 1-6, after the conductive agent carbon nanotubes are eliminated from the coating layer, although the slurry also contains the same proportion of carbon nanotube layers, the diaphragm resistance is significantly increased. It is speculated that when the nanotubes are in the functional coating layer, they can connect the adjacent inner and outer layers of the active material to reduce the polarization of the battery. It is found from the data of Examples 4-6 that adjusting the thickness or mass of each functional layer in the functional agent within a certain range is helpful for improving the overall performance of the entire battery.

[0164] In summary, embodiments 1 to 6 are superior to the existing solutions, and the design of the coating layer used enables the battery to have good comprehensive electrochemical performance.

[0165] It should be noted that, in this article, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "including one" do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0166] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode material, characterized in that: The material comprises a positive electrode active material (1) and a coating layer (2), wherein the coating layer is coated on the outer surface of the positive electrode active material; The coating layer (2) comprises coating material particles, the coating material particles have a core-shell structure, the core of the core-shell structure is an adsorption material (21), and the outer shell layer of the core-shell structure is a deoxidation material (22); the adsorption material (21) comprises a porous adsorption material.

2. The positive electrode material according to claim 1, characterized in that The coating layer (2) has a thickness of 0.5-3 μm; the coating material particles further include a liquid retaining material layer (23), and the liquid retaining material layer (23) is coated on the outer surface of the deoxidizing material (22).

3. The positive electrode material according to claim 2, characterized in that The mass ratio of the adsorption material (21), the deoxidation material (22) and the liquid retaining material layer (23) is (80-90): (5-10): (5-10); and / or, The liquid retaining material includes a mixture of one or more of polyacrylate, polyacrylic acid diethyl ester, and polymethyl methacrylate; and / or, The thickness of the liquid retaining material layer (23) is 200nm-1000nm.

4. The positive electrode material according to claim 1, characterized in that The porous adsorption material includes a mixture of one or more of porous carbon materials, porous MOF, porous ZIF, and porous silicon-carbon materials; and / or, the deoxidizing material (22) comprises a mixture of one or more of catechol, pyrogallol, p-methoxyphenol, cresol, tert-butylcatechol, p-phenylenediamine, polyethyleneimine, acetyl dopamine, ethylenediamine, and diphenylamine; and / or; The thickness of the outer shell layer formed by the deoxidizing material (22) is 50nm-200nm.

5. The positive electrode material according to claim 1, characterized in that The coating layer (2) further comprises a conductive agent and a binder, wherein the mass ratio of the coating material particles to the conductive agent and the binder is (90-95): (5-10): (2-5); and / or the conductive agent comprises a mixture of one or more of graphene, conductive graphite and carbon nanotubes; And / or, the binder includes a mixture of one or more of PVDF, PTFE, CMC, and PAA.

6. The positive electrode material according to claim 1, characterized in that The positive electrode active material (1) comprises a mixture of one or more of a nickel-cobalt-lithium manganese oxide ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide and a layered oxide compound; preferably, the positive electrode active material (1) comprises a LiNi x Co y High nickel ternary material of MnO2, wherein x≥0.

7.

7. A method for producing a positive electrode material, characterized in that: The method comprises: The first porous precursor material particles are prepared by synthesizing cobalt salt and 2-methylimidazole; preparing the first porous precursor material particles and the deoxidized material into coating material particles; Mixing the coating material particles with a conductive agent and a binder to obtain a coating layer material; The positive electrode material is prepared by coating the coating layer material on the surface of the positive electrode active material.

8. The method for producing a positive electrode material according to claim 7, characterized in that: The mass ratio of the cobalt salt to 2-methylimidazole is 1:(3-6); and / or, When the first porous precursor material particles and the deoxidizing material are prepared into coated material particles, a liquid retaining material is also added; and / or, The mass ratio of the coating material particles to the conductive agent and the binder is (90-95):(5-10):(2-5).

9. The method for producing a positive electrode material according to claim 7, characterized in that: The step of synthesizing the cobalt salt and 2-methylimidazole to prepare the first porous precursor material particles comprises: The cobalt salt and 2-methylimidazole are uniformly mixed in a solvent to prepare a mixed solution, and then the mixture is heated to react to synthesize a three-dimensional porous precursor material; Ball milling the three-dimensional porous precursor material to prepare first porous precursor material particles; and / or, The step of preparing the first porous precursor material particles, the deoxidizing material, and the liquid retaining material into coating material particles comprises: After uniformly dispersing the first porous precursor material particles into a solution containing a deoxidizing material, centrifugally filtering and air-drying to obtain second porous precursor material particles with the deoxidizing material adsorbed on the surface; The liquid-retaining material is ball-milled and uniformly dispersed in a solvent to prepare a polymer colloidal solution; The polymer colloidal solution is uniformly coated on the surface of the second porous precursor material particles by spray drying, and then heated and dried to obtain coated material particles.

10. The method for producing a positive electrode material according to claim 9, characterized in that: The solvent includes at least one of water, DMF, ethylene glycol and methanol; and / or, The concentration of the mixed solution is 10-100 g / L; and / or, The temperature of the temperature-raising reaction is 100-200°C, and the reaction time is 1-6h; and / or, The solvent in the solution containing the deoxidizing material is at least one of water, ethanol and methanol, and the concentration of the solution containing the deoxidizing material is 5-10 g / L; and / or, The spray drying temperature is 60-100°C.

Citation Information

Patent Citations

  • Anode active material, preparation method of anode active material, high-performance anode slurry containing anode active material, and all-solid-state lithium ion battery

    CN106784798A

  • Manganese-based metal organic framework compound-coated lithium ion battery ternary positive electrode material and preparation method thereof

    CN107910529A

  • Double-coated lithium battery positive electrode material and preparation method thereof

    CN112670514A

  • Surface-modified positive electrode material as well as preparation method and application thereof

    CN115881954A

  • Positive pole piece containing core-shell structure microspheres and battery

    CN116864613A